Distribution of di(2-ethylhexyl) phthalate and products in blood and blood components. - Rock, G (1986)
In order to impart flexibility, plastic medical devices incorporate liquid plasticizers into their structure. Data from several laboratories, including ours, have shown that these compounds leach from blood bags and tubing during collection of blood, storage of various blood components and during kidney dialysis and cell and plasma apheresis procedures. After the plasticizer di(2-ethylhexyl) phthalate leaches from poly(vinyl chloride) blood packs, it is converted by a plasma enzyme to a more toxic metabolite, mono(2-ethylhexyl) phthalate. Blood fractionation products from outdated plasma contain mono(2-ethylhexyl) phthalate, the highest level being found in normal serum albumin. Recently, we have reported that di(2-ethylhexyl) phthalate actually binds to the red blood cell membrane and reduces its osmotic fragility. Current methods of red cells storage, which permit utilization up to 35 days after collection, are not possible without this membrane stabilization. Platelets are now stored for 5 days in the Fenwal PL 732 polyolefin bag. Although stated to be essentially free of liquid plasticizers, a significant level of leaching from this bag into the extracts of stored platelet concentrates was observed.